Egressos do Projeto Social PRIMA no curso de música da UFPB - Souza, Jennifer Ferreira de (2022)
The Inclusion Through Music and Arts Program (PRIMA), has 24 teaching centers installed in 16 municipalities in Paraiba, the centers were designed to be inside state public schools in areas of social vulnerability, to bring citizenship and music. The present research sought to understand the importance of PRIMA for students who are in the music undergraduate course at UFPB. This research covered 24 undergraduate students from PRIMA, from different periods and age group from 15 to 30 years old, with different instruments. As a collection instrument, I used the survey for this research, in the form of a Google Form. Regarding the methodology, I used a qualitative approach to analyze data from the perspective of the participants. The results showed that students graduating from the Project have been approved in the selection for admission to UFPB in all semesters since 2015. Of these, 87.5% already work professionally even before graduation. Other results showed that, of the 24 graduates, only 13 receive institutional support to stay at the University. And 41.7% pointed out differences between teaching at PRIMA and at UFPB, such as the required repertoire and greater technical demand. We conclude that the Project is important for the citizenship and formation of new musicians, positively impacting both the UFPB and the orchestra organizations of the city of João Pessoa.